Modeling of 3D trajectory of Hayabusa2 re-entry based on acoustic observations - Nishikawa, Y.; Yamamoto, M.Y.; Sansom, Eleanor; Devillepoix, Hadrien; Towner, Martin; Hiramatsu, Y.; Kawamura, T.; Fujita, K.; Yoshikawa, M.; Ishihara, Y.; Hamama, I.; Segawa, N.; et al. (OXFORD UNIV PRESS, 2022)
On 2020 December 5 at 17:28 UTC, Japan Aerospace Exploration Agency's Hayabusa2 sample return capsule (SRC) re-entered Earth's atmosphere. The capsule passed through the atmosphere at supersonic speeds, emitting sound and light. The inaudible sound was recorded by infrasound sensors installed by Kochi University of Technology and Curtin University. Based on analysis of the recorded infrasound, the trajectory of the SRC in two cases, one with constant-velocity linear motion and the other with silent flight, could be estimated with an accuracy of 0° 5 in elevation and 1° in direction. A comparison with optical observations suggests a state of flight in which no light is emitted but sound is emitted. In this paper, we describe the method and results of the trajectory estimation.